KUALITAS PELAYANAN WAITER DI HOTEL ALPHA PEKANBARU - Gultom, Ryanson Christian; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of conducting this research is to know the service quality at Alpha Hotel Restaurant Pekanbaru. This research uses quantitative methode. Quantitative research is a systematic scientific study of parts and phenomena and their relationship. In this case the quality of service is good determine the development of restaurants in addition to food and beverages as a product offered. Alpha Hotel Restaurant Pekanbaru is a restaurant that has a quality service that has not been in accordance with the expected so that caused a lot of complains from guests. Based on the results of research that has been done responses of respondents stated that of the five dimensions of service quality to get good results from every guest who visit and who stay, the more dominant dimensions is the tangible dimension.Keywords : Restaurant, Service Quality, Waiter.